Feasibility and Implementation of Musculoskeletal Ultrasound Training in Occupational Medicine Residency Education. Issue 12 (December 2015) - Sayeed, Yusef; Marrocco, Antonella; Sully, Keziah; Werntz, Charles; Allen, Anna; Minardi, Joseph
Abstract : Objective: This article aims to present the musculoskeletal (MSK) ultrasound (US) course, the objective measures of occupational medicine (OM) resident skill, and subjective opinions of OM residents regarding the MSK US course and MSK US in general. Also, to provide other OM residency programs information to help them develop this skill for their programs. Methods: Didactic sessions based on American Institute of Ultrasound in Medicine (AIUM) guidelines were taught in modular format with subsequent practice-based workshops. A practical examination was given at the completion of the workshop and a survey of the residents experience during the workshop. Results: The average score on the practical examination among residents was 92.5%. The survey indicated that the residents felt like they learned from this course and increased their knowledge of MSK US. Conclusions: The findings suggest that a course in MSK US for OM residents can feasibly be implemented in an OM residency curriculum.